Adenocarcinoma of the small intestine complicating Crohn's disease. Issue 3 (March 1982) - Hawker, P C; Gyde, S N; Thompson, H; Allan, R N
Abstract : Adenocarcinoma of the small intestine is an uncommon complication of Crohn's disease. We report the clinical and pathological details of three cases diagnosed between 1968 and 1980 with a review of 58 cases from the literature. Of the 61 cases, 41 tumours occurred in the ileum, 18 in the jejunum, one in the duodenum and ileum, and one in the ileum and colon. Eighteen occurred in bypassed intestinal loops. The prognosis was poor: 44 patients (72%) had died with a mean interval of only 7.9 months from the diagnosis of cancer.